(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Rainwater harvesting and conserving technologies are essential interventions for water supply and food production in Kenya’s dry and semi-arid regions due to low soil moisture levels. Despite extensive study on the subject, variables influencing farmer acceptance and adaptation of these helpful technologies remain unknown, and low adoption and adaption levels of these beneficial technologies remain a problem. This study expands on this feature, focusing on the Tharaka South sub-county, where family food insecurity is exacerbated by water shortage, unpredictable rainfall, and soil water stress. A cross-sectional survey methodology was used to gather farm and social data from 351 household heads. Descriptive statistics and logistic regression were used to analyze the data. Trashlines (73 percent) used in situ rainwater collecting and saving methods more than micro-catchments (26 percent), Zai pits (26 percent), and Negarims (13 percent). Household size (p 0.01) and Zai pit training (p 0.002) were positively and substantially related with Zai pit usage, whereas overall farm size (p 0.01) and land tenure (p 0.01) had negative co-efficients. Rainwater collection and conservation technologies were disseminated using both official and informal teaching methods. Farmers’ age, family size, farm size, farming history, training, and formal education were shown to be significant variables influencing the adoption of rainwater collecting and saving technology in Tharaka sub-county, according to the research. In contrast to less resource intensive technologies, specific methods are required to increase the efficiency of asset technology.